Ethics of legal supervision and auditing in the Islamic banks - Daraghmi, Fadi Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
In this research, I covered the issue of (Sharia) supervision over Islamic financial institutions and banks, showing its definition, divisions, and Shari’s adaptability, functions, and objectives, in the research, I was solicitous in revealing the importance of these ethics and the role of oversight and Sharia audit in obtaining necessary data and information that would support and develop the audit process. And to clarify that the identity of Islamic banks is not separate from conventional banks except by the presence of a Sharia Supervisory Board, which monitors the compliance of these banks with the provisions of Islamic Sharia, Also, the achievement of quality in banking work is accomplished through the effectiveness of Sharia audit and the efficiency of both the observer and the auditor, Therefore, this research questioned the lack of effectiveness of the supervisory bodies in many Islamic banks, It requires a discussion of the conditions for performing its function in enriching the jurisprudence of Islamic transactions, Improving the formulas, services, and contracts of financial institutions and highlighting the complementary function of the Sharia auditor with the supervisory authority in reducing the error of jurisprudential reduction and the risks of fraud and doctrinal fraud, Strengthening the descriptive approach through my study of university theses and Arabic books, as well as I followed the analytical approach to reach the required results, and the research was divided into several sections.
Keywords: Sharia audit; Analytical method; Sharia Supervision; jurisprudential reduction; Fictitious contract; traditional expenses